Mapping the Research Landscape of Social Media Strategies for Brand Awareness: A Bibliometric Analysis - Rahmadani, Aulia; Sutirman, Sutirman; Wijaya, Tony (PT FORMOSA CENDEKIA GLOBAL, 2025)
This study examines the development of the global literature related to social media strategies in building brand awareness through bibliometric analysis of 122 Scopus articles (2009–2025). Using VOSviewer, this study maps publication trends, collaboration networks, geographic distribution, and thematic clusters by keyword. The results show a significant increase in publications since 2020, with the dominance of contributions from the United States, India, and the United Kingdom. Eight main clusters were identified, including purchase intent, influencer marketing, and e-WOM. This study makes a theoretical contribution to the mapping of the digital marketing literature and offers practical implications for MSME actors in utilizing social media to strengthen brand positions, as well as encouraging global research collaboration in the era of digital transformation.